Simulation and analysis of the possibilities of traction electric motor - Ayman Al-Rawashdeh (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Great efforts are directed to word the use of electrical vehicles in transportation. Mathematical modeling tools can provide a powerful approach for investigating electrical vehciles and are successfully implemented by applying Matlab/Simulink. In this paper, the mathematical simulation model of Series Excited DC motor (tractive motor) on Matlab/Simulink was implemented and investigated. The main objective of this study is to assess the use of Series Excited DC motor (tractive motor) to be used for the new Amman city express bus project and evaluation of its performance characteristics in different running and loading cases. All simulation results are plotted and discussed. This study confirms the feasibility for the use of series excited DC motor (tractive motor) in electric buses as alternatives for sustaibale and environmentally friendly transportation system.